DAMPAK ASESMEN BERBASIS KARAKTER KEJUJURAN TERHADAP PENGAMBILAN KEPUTUSAN ETIS DALAM AKTIVITAS PEMBELAJARAN KELAS 3 MSI 05 SAMPANGAN - Rizal, Moch. (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to explore in depth the impact of honesty character-based assessment on ethical decision-making of grade 3 MSI 05 Sampangan students in learning activities. Honesty, as a fundamental ethical pillar, is believed to be essential in shaping individual moral behavior from an early age. Traditional assessment methods in elementary education often do not explicitly touch on the character dimension, raising questions about the effectiveness of instilling ethical values. Therefore, through a qualitative approach with a case study, this study seeks to understand how the implementation of an assessment that emphasizes honesty affects the way grade 3 MSI 05 Sampangan students understand ethical dilemmas, reflect on moral values, and ultimately, make responsible decisions during the learning process. Data were collected through participatory observations in the classroom, in-depth interviews with teachers and selected students, and document analysis related to honesty assessment practices in the classroom. The case study approach allows researchers to explore rich experiences, perceptions, and interactions in the natural context of the classroom. The findings are expected to reveal the psychological and social mechanisms behind changes in students' ethical behavior, contributing to a more comprehensive understanding of the effectiveness of character assessment. The results of this study are expected to be a practical guide for the development of more effective character education strategies in elementary schools, especially in the Sampangan area, in order to form a young generation that is not only intelligent, but also has high integrity. ABSTRAKPenelitian ini bertujuan untuk mengeksplorasi secara mendalam dampak asesmen berbasis karakter kejujuran terhadap pengambilan keputusan etis siswa kelas 3 MSI 05 Sampangan dalam aktivitas pembelajaran. Kejujuran, sebagai pilar etika fundamental, diyakini esensial dalam membentuk perilaku moral individu sejak usia dini. Metode asesmen tradisional di pendidikan dasar seringkali belum menyentuh dimensi karakter secara eksplisit, menimbulkan pertanyaan mengenai efektivitas penanaman nilai etis. Oleh karena itu, melalui pendekatan kualitatif dengan studi kasus, penelitian ini berupaya memahami bagaimana implementasi asesmen yang menekankan kejujuran memengaruhi cara siswa kelas 3 MSI 05 Sampangan memahami dilema etis, merefleksikan nilai-nilai moral, dan pada akhirnya, mengambil keputusan yang bertanggung jawab selama proses belajar. Data dikumpulkan melalui observasi partisipatif di kelas, wawancara mendalam dengan guru dan beberapa siswa terpilih, serta analisis dokumen terkait praktik asesmen kejujuran di kelas tersebut. Pendekatan studi kasus memungkinkan peneliti untuk menggali pengalaman, persepsi, dan interaksi yang kaya dalam konteks alami kelas. Temuan diharapkan dapat mengungkap mekanisme psikologis dan sosial di balik perubahan perilaku etis siswa, memberikan kontribusi pada pemahaman yang lebih komprehensif mengenai efektivitas asesmen karakter. Hasil penelitian ini diharapkan dapat menjadi panduan praktis bagi pengembangan strategi pendidikan karakter yang lebih efektif di sekolah dasar, khususnya di wilayah Sampangan, guna membentuk generasi muda yang tidak hanya cerdas, tetapi juga berintegritas tinggi.